Coupled coincidence point theorems for a (β, g)-ψ-contractive mapping in partially ordered g-metric spaces - Chaiporn Thangthong (2018)
© 2015 by the Mathematical Association of Thailand. All rights reserved. In this paper, we introduce the notion (β)-admissible and (β, g)- admissible for mapping F: X ×X → X and g: X → X. We showed the existence of a coupled coincidence point theorem for a (β, g)-ψ-contractive mapping in G-metric spaces. We also show the uniqueness of a coupled common fixed point for such mappings and give some examples to show the validity of our result.